Identifikasi jenis penyakit dan prevalensi penyakit karang pada terumbu karang diperairan pemuteran - Putu Hernanda Krishna Ariszandy; I Dewa Nyoman Nurweda Putra; Widiastuti Widiastuti (Journal of Marine Research and Technology, 2020)
Coral reef ecosystems play an important role in many aspects of human beings as one third of Indonesian population are living in coastal areas and depend their lives on this ecosystem. However, this ecosystem is threatened by various factors, one of them is coral disease. Increased sea water temperature, sedimentation, and pollutants can increase the growth of pathogenic microorganisms that cause coral disease. The data of coral diseases was collected byqpurposive samplingpmethod which was chosen based on the presence of coral reefs and coastal conditions at each station in a belt transect of 20 x 2 m. Furthermore, coral diseases and coral species were identified based on identification books. The prevalence of coral disease was calculated by divided the total number of coral colonies with the total number of diseased coral then multiplied by 100%. Results showed that the highest coral disease prevalence were at site 3 and 4. Meanwhile, site 1 and 2 were lower than those sites. It was suggested that the coral disease prevalence is related to the domestic input from the coastal. As site 1 and 2 were relatively low populated than site 3 and 4.